2007
DOI: 10.2139/ssrn.1685847
|View full text |Cite
|
Sign up to set email alerts
|

Downward Wage Rigidity for Different Workers and Firms: An Evaluation for Belgium Using the IWFP Procedure

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(38 citation statements)
references
References 107 publications
6
31
1
Order By: Relevance
“…At odds with these theoretical predictions, the estimated measures of nominal wage rigidity of immigrants from CEEC, Brazil and China are above those of native workers. However, this result is in line with other studies that found that nominal wage rigidity tends to be high at the bottom of the earnings distribution (see (Du Caju et al 2007) for Belgium). The estimated measures of real wage rigidity of the different immigrant groups are above those of native workers, but the difference is very small in the case of PALOP workers.…”
Section: Accounting For Heterogeneity By Immigrant Originsupporting
confidence: 93%
See 2 more Smart Citations
“…At odds with these theoretical predictions, the estimated measures of nominal wage rigidity of immigrants from CEEC, Brazil and China are above those of native workers. However, this result is in line with other studies that found that nominal wage rigidity tends to be high at the bottom of the earnings distribution (see (Du Caju et al 2007) for Belgium). The estimated measures of real wage rigidity of the different immigrant groups are above those of native workers, but the difference is very small in the case of PALOP workers.…”
Section: Accounting For Heterogeneity By Immigrant Originsupporting
confidence: 93%
“…In contrast, as discussed in (Du Caju et al 2007), the cost of losing a job is higher for older workers and workers with higher tenure. These workers have, therefore, less incentive to shirk or quit, even in presence of wage cuts, implying a higher likelihood of a wage cut for them and, thus, lower wage rigidity.…”
Section: Motivationmentioning
confidence: 94%
See 1 more Smart Citation
“…Second, recent evidence on downward wage rigidity in Belgium can be found in Dickens et al (2006Dickens et al ( , 2007, Du Caju et al (2007) and Knoppik and Beissinger (2005). These papers point to high downward real wage rigidity in Belgium.…”
Section: Introductionmentioning
confidence: 95%
“…This analysis, however, is subject to the caveat that wage rigidities at the firm level might be correlated with other firm characteristics, in particular firm size. Du Caju, Fuss, and Wintr (2007) find that wage rigidity is much higher for small firms, as large firms usually have firm-level collective wage agreements which enhances wage flexibility. Similarly, Avouyi-Dovi, Fougére, and Gautier (2013) report that negotiating wages is more costly for small firms, resulting in a lower frequency of wage changes.…”
Section: B Affected Firms With Rigid Wages Versus Affected Firms Witmentioning
confidence: 88%